Implementasi Meja 5 Plus pada Seluruh Siklus Kehidupan - Rahmi Pramulia Fitri; Denti Pertiwi; Nofriandi; Hermawarni Br Harahap; Dini Fitriyanni; Asti Alimah (HEALTH CARE: JURNAL KESEHATAN, 2025)
The life-course approach emphasizes that health interventions for the elderly are vital for maintaining functional capacity and quality of life. This study examines the implementation of the Meja 5 Plus system at community health posts specifically for older adults. The integration includes specialized nutrition services, clean and healthy living behavior (PHBS) education, and reproductive health counseling. Findings indicate that these comprehensive services effectively address degenerative disease prevention and nutritional fulfillment tailored to physiological changes. However, the program faces challenges such as limited volunteer capacity and resource availability in community settings. Strengthening cadre training and multi-sectoral support remains essential for the long-term sustainability of elderly health services.